A popular dictionary of Paganism - Pearson, Joanne, 1969- (RoutledgeCurzon, 2002)
This dictionary provides a readily available collection of source material for a subject which has recently become of considerable public and academic interest. It provides a point of reference for key words and concepts which have previously been available only in short glossaries, footnotes, or within a body of text. It deals with concepts shared by all Pagans, and also with those concepts unique to a particular Pagan tradition.